Nurses’ Knowledge on the Prevention of Ventilator-Associated Pneumonia (VAP) among Critically Ill Patients - Maha Sanat Alreshidi; Fareda Ali AlRashidi; Cyruz P. Tuppal; Nojoud Al Rashidi; Denise Angelo M. Prudencio; Rico William A. Villagracia; Hazel N. Villagracia (Nurse Media: Journal of Nursing)
Background: Ventilator-associated pneumonia (VAP) is a significant concern in healthcare settings, particularly among critically ill patients who require mechanical ventilation. Nurses play a vital role in preventing VAP through their knowledge and implementation of evidence-based practices. However, there exists a notable gap in the research regarding nurses’ knowledge of preventing VAP to improve patient outcomes and reduce healthcare costs.